2000
DOI: 10.1086/312752
|View full text |Cite
|
Sign up to set email alerts
|

Planet Formation is Unlikely in Equal-Mass Binary Systems with [CLC][ITAL]a[/ITAL][/CLC] ∼ 50 AU

Abstract: We show that planet formation via both gravitational collapse and core accretion is unlikely to occur in equal mass binary systems with moderate (∼ 50 AU) semimajor axes. Internal thermal energy generation in the disks is sufficient to heat the gas everywhere so that spiral structures quickly decay rather than grow or fragment. This same heating will inhibit dust coagulation because the temperatures rise above the vaporization temperatures of many volatile materials. We consider other processes not included in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
242
8

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(258 citation statements)
references
References 27 publications
8
242
8
Order By: Relevance
“…Problems could also arise at even earlier stages. Nelson (2000) has for instance shown that, under certain conditions, thermal energy dissipation in gas disks for equal mass binaries could inhibit dust coagulation by raising temperatures above vaporization limit. But, as recognized by the author himself, these results are still preliminary, and a complete study of this problem, taking into account a broader range of physical parameters, has yet to be carried out.…”
Section: Do Planetesimals Really Form?mentioning
confidence: 99%
“…Problems could also arise at even earlier stages. Nelson (2000) has for instance shown that, under certain conditions, thermal energy dissipation in gas disks for equal mass binaries could inhibit dust coagulation by raising temperatures above vaporization limit. But, as recognized by the author himself, these results are still preliminary, and a complete study of this problem, taking into account a broader range of physical parameters, has yet to be carried out.…”
Section: Do Planetesimals Really Form?mentioning
confidence: 99%
“…A stellar companion within 100 AU probably affects the formation of giant planets (e.g., Nelson 2000;Mayer et al 2005;Thébault et al 2006;and others).…”
Section: Introductionmentioning
confidence: 99%
“…Its shape is expected to be elliptic with varying eccentricity Paardekooper et al 2008;Kley & Nelson 2008). Both these features may alter the dust sedimentation process on the mid plane of the disk and the grain accumulation into planetesimals which might even be inhibited (Nelson 2000). More eccentric trajectories of the grains, dragged by the gas, increase the impact rate but, on the other hand, might lead to destructive collisions by increasing the relative velocity.…”
Section: Introductionmentioning
confidence: 99%